Microstructure and mechanical property of friction stir welded Al-Mg joints by adopting modified joint configuration technique. (2020) - kumar, Uday; Acharya, Uttam; Saha, S.C.; Saha Roy, Barnik
Abstract: Friction Stir Welding (FSW) is a solid-state manufacturing process that has remarkably enhanced the joint quality of the Al-Mg dissimilar joint. In this paper, a spick-and-span joint configuration has been introduced that has impressively welded modified joint configuration. While welding precise control of welding parameters and plate setup are the most important factors that have governed the strength of the Al-Mg joint. Mechanical interlocking at the faying surface and the bonding between the dissimilar metals are the two noticed joining mechanism. At tool rotational speed of 600 rpm and tool travel speed of 0.75 mm/s maximum tensile strength of 147 MPa was obtained with a joint efficiency of 61%. Also, at this parameter martial movement from shoulder influenced region to pin influenced region has been spotted. Further, to realize the intermetallic formation in welding zone XRD analysis has been performed and major intermetallic compound of Al3 Mg2 and Al12 Mg17 was noticed.